Sexually Transmitted Infections in the context of deprivation of liberty (Research, Society and Development, 2021)
Identify self-reported and confirmed cases of STI in women deprived of their liberty. This is an exploratory, descriptive, cross-sectional case study with a quantitative approach, performed with 62 women from the Prison Complex of Santarém, Pará. The results showed that 56,5% of the women had low schooling, 91,9% declared themselves to be black and brown-skinned, 59,7% were in the age group of 21 to 40 years, 59,7% said they did not use a condom. The prevalence of self-reported STI was 25,8% (syphilis and gonorrhea), but 19,4% of syphilis cases and 7.0% of HPV cases were identified and confirmed, no other STI were identified in the study. It was noted how distant the Brazilian prison system is from the humanitarian ideal, besides the need to recognize women in deprivation of liberty as capable of making decisions about their bodies and their health, in this sense, it is fundamental that these women, have dignified conditions and opportunities for health promotion and education about STI, as well as services within the principles guaranteed by public policies, of accessibility, completeness, resolution and humanization of health care.